Fractal Loading Model of the Joint Interface Considering Strain Hardening of Materials - Yanhui Wang; Xueliang Zhang; Shuhua Wen; Yonghui Chen (Advances in Materials Science and Engineering)
Based on fractal geometry theory, the deformation state of the four stages of the asperity elastic, first elastoplastic, second elastoplastic, and fully plastic deformation and comprehensively considering the hardness of the asperity changes with the amount of deformation in elastoplastic deformation stage due to strain hardening are considered, thereby establishing a single-loading model of the joint interface. By introducing the pushing coefficient and the asperity frequency exponent, each critical frequency exponents of asperity is obtained, and the relationship between the normal contact load and the contact area of the first elastoplastic deformation phase and the second elastoplastic deformation phase of the single asperity in the case of taking into account the change in hardness is inferred, eventually deducing the relationship between the total contact load of the joint interface and the contact area. The analysis results show that in the elastoplastic deformation stage, when the deformation is constant, the asperity load considering the hardness change is smaller than the unconsidered load, and the difference increases with the increase of the deformation amount. The establishment of the model provides a theoretical basis for further research on the elastoplastic contact of joint interfaces.